1996
DOI: 10.1017/s0263574700019639
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of a high-performance haptic interface

Abstract: SUMMARYA haptic interface is a computer-controlled mechanism designed to detect motion of a human operator without impeding that motion, and to feed back forces from a teleoperated robot or virtual environment. Design of such a device is not trivial, because of the many conflicting constraints the designer must face.As part of our research into haptics, we have developed a prototype planar mechanism. It has low apparent mass and damping, high structural stiffness, high force bandwidth, high force dynamic range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(77 citation statements)
references
References 12 publications
1
75
0
1
Order By: Relevance
“…Some of these methods employ only algorithm validation and comparison based on rendering realism [5], [6], whereas some others studied control design and evaluation for haptic interfaces [7], [8], [9]. Several projects [10], [11] evaluated particular haptic devices based on technical performance metrics given by Hayward and Astley [12]. There are many human factor studies to asses the benefits of haptic feedback on sensory-motor control tasks.…”
Section: A State Of the Artmentioning
confidence: 99%
“…Some of these methods employ only algorithm validation and comparison based on rendering realism [5], [6], whereas some others studied control design and evaluation for haptic interfaces [7], [8], [9]. Several projects [10], [11] evaluated particular haptic devices based on technical performance metrics given by Hayward and Astley [12]. There are many human factor studies to asses the benefits of haptic feedback on sensory-motor control tasks.…”
Section: A State Of the Artmentioning
confidence: 99%
“…Another largely overlooked factor is maximum acceleration. In emulating stiff walls, for example, the maximum acceleration is critical yet only a couple of the haptic devices we studied gave this performance measure [6].…”
Section: A Plethora Of Performance Measuresmentioning
confidence: 99%
“…It is a challenging computational problem due to the high dimensionality of the underlying search Interactive systems provide a 3D virtual environment, where the user interacts with the virtual molecules, and performs a knowledge-guided search and selection 15 of the final binding pose. Interactive docking is not able to search a large number of docking pairs as in automated docking.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that such docking systems can reduce incorrect binding poses [10], and improve the users' (experts or students of structural biology) understanding of the process of molecular binding [11,12]. sponses, modern haptic technology requires haptic feedback cues to be updated at a refresh rate of 500Hz to 1 kHz due to the sensitivity of the human haptic system [13] [14] [15]. When this rate is not met device vibrations and force discontinuities can occur limiting practical use.…”
Section: Introductionmentioning
confidence: 99%